Intention to Halal Tourism: The Influence of Religiosity and Personal Efficacy - Erni Cahyaningsih; Anton Priyo Nugroho (Universitas Muhammadiyah Magelang, 2022)
In Yogyakarta, there are many tourist attractions, but none of them have halal tourism destinations. To achieve this, it needs support from various parties, including tourists with an intention in halal tourism, which is closely related to their obedience to their religion. The intention in performing behavior had influenced by attitudes, subjective norms, and self-efficacy. This study used a quantitative approach and the data analysis method used was multiple linear regression analysis. The results indicated that tourist religiosity had a positive and significant effect on halal tourism in Yogyakarta. In contrast, attitudes, subjective norms, and self-efficacy of tourists showed no positive and significant effect on the intention of halal tourism in Yogyakarta.